Luke's characters in their Jewish world: being Theophilus - Read-Heimerdinger, Jenny (The Library of New Testament Studies, 2024)
"Jenny Read-Heimerdinger explores the characters of Luke-Acts in order to situate them in the Jewish world to which they belong. Through a close reading of the Greek text, she argues that Luke emerges as a person thoroughly steeped in a Jewish view of Scripture, familiar with a range of associated oral traditions; and that taking account of the Jewish features allows new insights into the way that the author situates events and characters firmly within the history of Israel, before the Church was a separate institution or religion. Read-Heimerdinger proposes that such a view of his work implies an addressee capable of understanding what he received and that one eminently qualified candidate is Theophilus, the high priest in Jerusalem 37-41 and brother-in-law of Caiaphas. The Jewish perspective of Luke's two volumes is more visible in forms of the text not used for modern translations, notably that of Codex Bezae and the early versions, which are rejected by the editors of the Greek New Testament on which translations are based. Read-Heimerdinger draws on the analysis of the variants of the Greek text analysed in her previous Luke in his Own Words (2022), in a manner more accessible to readers unfamiliar with Greek. The variant readings make use of a sophisticated knowledge of Jewish exegetical techniques that would generally be discarded by later generations of Christians but which are increasingly being recognized by NT scholars, in line with Jewish historical studies of Second Temple and Rabbinic Judaism. Seeing the characters of Luke-Acts through Theophilus' eyes brings exciting insights and a fresh understanding of the author's message." --